The use of lipid-based nanocarriers for targeted pain therapies - Hua, Susan; Wu, Sherry Y. (Frontiers in Pharmacology, 2013)
Sustained delivery of analgesic agents at target sites remains a critical issue for effective pain management. The use of nanocarriers has been reported to facilitate effective delivery of these agents to target sites while minimising systemic toxicity. These include the use of biodegradable liposomal or polymeric carriers. Of these, liposomes present as an attractive delivery system due to their flexible physicochemical properties which allow easy manipulation in order to address different delivery considerations. Their favourable toxicity profiles and ease of large scale production also make their clinical use feasible. In this review, we will discuss the concept of using liposomes as a drug delivery carrier, their in vitro characteristics as well as in vivo behaviour. Current advances in the targeted liposomal delivery of analgesic agents and their impacts on the field of pain management will be presented.